Optimization Approach on Planning Balance Nutrient Intake for Secondary School Students Aged 16 to 18 - Mohd Nazri, Mohamad Azam; Sufahani, Suliadi Firdaus (Enhanced Knowledge in Sciences and Technology, 2024)
This study presents optimization approach to plan a balanced nutrient intake for Malaysian secondary school students aged sixteen to eighteen. The aim of this study is to minimize the cost of daily food intakes and to provide a practical tool for schools and institutions responsible for planning menus for students. In this study, linear programming, integer programming, and binary programming are applied to solve the diet problem of Malaysian students aged 16 to 18 using a mathematical model. The objective function of the meal planning model is to minimize the cost of food while meeting the recommended nutrient. The results revealed that the optimal solution achieved through integer programming shows a minimum cost of RM 10.10 per day for a nutritious diet suitable for secondary students who are moderately active and students who are active in sports. Furthermore, the study contributes to the theoretical foundation by addressing the challenge of repetition in meal plans, emphasizing the importance of diverse food choices for promoting healthier eating practices among students.